A Scoping Review of the Health of African Immigrant and Refugee Children (2021)
Migration is a growing phenomenon around the world, including within the African continent. Many migrants, especially African children, face challenges related to health and social in-clusion and can face increased health risks. A systematic scoping review of available literature on the health of African migrant children across the globe was conducted to offer insight into these health risks. The review was conducted over a 15-month period from January 2019 to April 2020, yielding 6602 articles once duplicates were removed. This search included electronic databases, reference lists of articles reviewed, and searches of libraries of relevant organisations. A total of 187 studies met the inclusion criteria, of which 159 were quantitative, 22 were qualitative, and 6 used mixed methods. The findings reveal decreased health in this population in areas of nutrition, infectious diseases, mental health, birth outcomes, sexual and reproductive health, physical and developmental health, parasitic infections, oral health, respiratory health, preventative health, endocrine disorders, health care services, and haematological conditions. The findings offer insights into factors influencing the health of African immigrant and refugee children. Further studies, especially qualitative studies, are needed to determine barriers to service access after migration and to investigate other underexplored and overlooked health concerns of African migrant children, including pneumonia and child maltreatment.